Indian economic, planning: three decades of development - Uppal, J. S. (Delhi, 1984)
India is a pioneer in initiating economic planning among the third world developing countries. A study of India's development experience is of crucial importance, not only for students of Indian economy but also for third world countries whose develop ment plans are fashioned after the Indian experiment in planning. India has now completed three decades of economic planning. In this book the outcome of these three decades of planning has been analysed comprehensively using the latest statistical information and incorporating various explanations offered for achievements and failures of India's plans. In essence. the book tries to provide an answer to the often raised question: whatever has come out of thirty years of Indian economic planning?
Keywords: Economic policy